Pergerakan Autonomous Pesawat Tanpa Awak Berdasarkan Tinggi Terbang Pesawat - Kurniadi Ilham; Riki Mukhaiyar (Ranah Research : Journal of Multidisciplinary Research and Development, 2021)
Not much different from the working principle of ordinary aircraft, Unmanned Aircraft also uses an airfoil design on the wings to be able to manipulate aerodynamics so that the aircraft can fly. it's just that airplanes are usually controlled by pilots while Unmanned aircraft are controlled remotely connected by radio signals. To carry out its rift mission, the aircraft is equipped with an autonomous system by determining way-points assisted by GPS so that later the aircraft can fly more precisely than manually controlled directly by humans. When flying automatically, the aircraft is often constrained by failed take-offs and when flying on missions the position of the aircraft making turns (Loop Maneuver) is often imprecise. Therefore, the time taken by the aircraft to perform the loop maneuver is calculated using the circle circumference formula and divided by the average speed of the aircraft.